Persepsi Siswa tentang Pemahaman Keterampilan dan Konsep Bola Basket dalam Pendidikan Jasmani: Studi Kasus di Sekolah Kejuruan Al Azhar 02 Tekraf - Dhika Bayu Mahardhika; Tedi Purbangkara; Dikdik Fauzi Dermawan; Alam Hadi Kosasih; Bela Santika (Indonesian Journal of Physical Education and Sport Science, 2026)
Study Purpose. This study aims to analyze students’ perceptions of their understanding of basketball learning at Al Azhar 02 Tekraf Vocational School, with attention to how teaching methods, learning environment, and instructional strategies shape students’ comprehension and engagement. Materials and Methods. This study employed a descriptive quantitative design. The population consisted of students of Al Azhar 02 Tekraf Vocational School who participated in basketball learning during the second semester of the 2024–2025 academic year. Using purposive sampling, 60 students with direct experience in basketball classes were selected as respondents. Data were collected using a structured questionnaire based on a five-point Likert scale to assess students’ perceived understanding, motivation, and learning experiences in basketball learning. The instrument was reviewed through expert validation and refined through pilot testing prior to its administration. The data were analyzed using descriptive statistics, including frequencies, percentages, mean scores, and standard deviations, to identify patterns and trends in students’ perceptions. Results. Students generally reported positive perceptions of learning basketball. 1) They appreciated clear teacher explanations, demonstrations, and opportunities for active practice. 2) Emotional support, peer collaboration, and 3) Adequate facilities were also perceived as enhancing motivation and participation. However, although students felt confident in performing physical skills, some reported difficulty understanding complex game strategies, indicating gaps in cognitive and tactical understanding. Conclusions. Effective teaching methods, interactive learning environments, and supportive teacher peer relationships contribute to stronger student understanding and enjoyment of basketball learning. Strengthening cognitive instruction especially on tactics and game strategy may further improve learning outcomes in vocational school physical education contexts.